Correlation between Knowledge, Sleep Patterns, Diet, Inhibitors, and Enhancers with Anemia Incidence in Young Girls at Al-Amanah Al-Gontory Islamic Boarding School in 2023: Hubungan Pengetahuan Anemia, Pola Tidur, Pola Makan, Inhibitor, dan Enhancer dengan Kejadian Anemia pada Remaja Putri di Pondok Pesantren Al-Amanah Al-Gontory Kota Tangerang Selatan - Handini, Kania Noviyanti; Ilmi, Ibnu Malkan Bakhrul; Simanungkalit, Sintha Fransiske; Octaria, Yessi Crosita (Universitas Airlangga, 2023)
Background: The prevalence of anemia among adolescents in Indonesia in 2018 was approximately 32%. Adolescent girls are ten times more likely to experience anemia than adolescent boys. Anemia can be influenced by knowledge, sleep patterns, dietary pattern, inhibitors, and enhancers. Objectives: To analyze the relationship between knowledge, sleep patterns, dietary patterns, inhibitors, and enhancers with the incidence of anemia in adolescent girls at Al-Amanah Al-Gontory Islamic Boarding School South Tangerang City. Methods: This study used a cross-sectional design with 113 samples selected using a stratified random sampling technique. Data analysis used the Chi-Square test and Fisher's Exact. Results: There was a relationship between sleep patterns (p=0.003), protein intake (p=0.000), iron intake (p=0.000), and inhibitors (p=0.000) and the incidence of anemia and there was no relationship between knowledge (p = 0.156) and enhancer (p = 0.970) with the incidence of anemia. Conclusions: Anemia can be influenced by a person's sleep patterns. Poor sleep patterns are related to sleep disturbances, lack of sleep, and drowsiness. A person's diet (iron and protein) and frequent consumption of inhibitors can also cause anemia.